Validation of the Personal Responsibility Scale: Rasch Model Analysis - Handaka, Irvan Budhi; Taufiq, Agus; Yusuf, Syamsu; Herdiansyah, Diki; Septikasari, Zela (Jurnal Kajian Bimbingan dan Konseling, 2024)
Increasing personal responsibility in education is an innovative idea, an idea to educate students in developing morals and values, or the basis of character education. This research aims to develop a personal responsibility scale for students which is expected to become a valid and reliable measuring tool. The method used in this research is a quantitative approach and data analysis used using the Rasch model. The research population consisted of 309 students as respondents, then the sampling technique was purposive sampling with a total of 20 students. The research results showed that the personal responsibility scale was declared suitable for use based on statistical tests using Rasch mode with a reliability value of 0.81. So based on the results of this analysis it can be used as an instrument to measure students' personal responsibility. The implications of the validation results of the personal responsibility instrument are useful in measuring students' personal responsibility, as a basis for providing guidance and counseling services.